The Suitability of the Concept of Muzara’ah in the Practice of Dhu'um Labengan Tobacco Plants in the Perspective of Islamic Law - Maulida, Okty Nur; Busro Karim, Busro (Et-Tijarie, 2024)
The main problem faced by the community in East Duko village is related to the work of land for tobacco plants. The purpose of this study is to analyze the practice of dhu'um labengan tobacco plants based on the concept of muzara’ah from the perspective of Islamic law. This research is a type of qualitative research, field research that is descriptive analysis, the object of this research is the practice of agricultural cooperation in the village of Duko Timur, Larangan, Pamekasan. The data collection methods used are interview and documentation methods. From the results of the study, it was found that there was a practice of dhu'um labengan tobacco plants. The results of this study can be concluded that most people in East Duko Village carry out this practice in accordance and can be said to be legal, because they have met the principles and valid requirements of the muzara'ah contract and have become a custom in East Duko Village. The results of this study give implications that the practice of dhu'um can be applied to the community in East Duko village in accordance with the agreements and customs contained in the community. The recommendation that can be given from this study is that the practice of dhu'um can be carried out in any village in accordance with the rules that apply in the community.